Towards 13 Years of Compulsory Education: Strategies for Equitable Access to Quality Education in Indonesia - M. Reza Saputra; Nabila Hilyatunisa (Journal of Smart Pedagogy and Education, 2025)
The transition to a thirteen-year compulsory education system in Indonesia presents a critical opportunity to strengthen academic learning outcomes and promote inclusive, high-quality education. Despite high primary enrollment rates, significant retention gaps emerge at junior and senior secondary levels, particularly in rural and 3T (frontier, outermost, and disadvantaged) regions. This study aims to identify the key barriers to academic progression and propose evidence-based strategies to enhance educational equity and quality across diverse socioeconomic contexts. Employing a mixed-methods approach, we conducted a systematic review of peer-reviewed literature, analyzed national and provincial enrollment and completion statistics, and carried out case studies in representative 3T districts to assess infrastructure, teacher capacity, and learner support mechanisms. Our findings reveal that disparities in school facilities, teacher qualifications, and digital infrastructure critically undermine academic achievement, while early childhood education (PAUD) expansion and the Merdeka Belajar reform offer promising pedagogical and policy frameworks. We further demonstrate that targeted resource allocations, comprehensive teacher professional development, and community-engaged governance models significantly improve student retention and performance. The synthesis of quantitative and qualitative evidence informs a set of actionable recommendations, including scalable PAUD integration, adaptive curriculum design, and sustainable funding mechanisms aligned with demographic dividend objectives. These insights provide a roadmap for policymakers and educators to implement a thirteen-year compulsory education system that not only extends academic access but also elevates learning quality and lifelong competencies.